Association of Kaposi's sarcoma associated herpesvirus (KSHV) DNA in bronchoalveolar lavage fluid of HIV infected individuals with bronchoscopically diagnosed tracheobronchial Kaposi's sarcoma. Issue 1 (February 1998) - Howard, M R; Brink, N S; Whitby, D; Tedder, R S; Miller, R F
Abstract : OBJECTIVES: To determine the frequency of detection of Kaposi's sarcoma associated herpesvirus (KSHV), also known as human herpesvirus (HHV) type 8, DNA in bronchoalveolar lavage (BAL) fluid from HIV infected individuals with and without KS and to compare this with the detection rate in peripheral blood. Also to identify whether KSHV was associated with specific cell types in lavage fluid. METHODS: Nested PCR was used to detect KSHV DNA in BAL fluid from 41 consecutive individuals with Kaposi's sarcoma (KS) and in 41 controls with similar CD4 lymphocyte counts. Semiquantification of viral DNA was by end point titration. A positive cell sorting selection procedure was used to isolate specific BAL fluid cell types. RESULTS: KSHV DNA was detected in BAL fluid from 24 of 29 (83%) individuals with a bronchoscopic diagnosis of tracheobronchial KS. None was detected in 12 individuals with only cutaneous KS, or in 41 matched controls without KS. In five, KSHV DNA was detected in the cell depleted and cellular fractions of BAL fluid and in 1/5 in the CD14 (macrophage) fractions. None was detected in the CD19 (B lymphocyte) or CD4/CD8 (T lymphocyte) fractions. CONCLUSIONS: There was a clear association between the diagnosis of tracheobronchial KS and detection of KSHV DNA in BAL fluid. The cell type supporting KSHV in the respiratory tract is not CD 19 positive and has yet to be conclusively identified.